Partisipasi Pendidikan Menengah Atas dan Perkawinan Remaja Perempuan 16–18 Tahun di Indonesia - Wicaksono, Herjuno Bagus; Setyonaluri, Diahhadi (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
This study examines the relationship between upper secondary education participation and early marriage among women aged 16–18 in Indonesia. Using district-level panel data for 2014–2023, the analysis applies a fixed effects regression to estimate the association between the female net enrollment rate and marriage prevalence among adolescent women. The results indicate that higher participation in upper secondary education is associated with lower early marriage rates. Socioeconomic factors and the implementation of the Marriage Law Reform are also relevant contributors. These findings suggest the importance of expanding access to upper secondary education as part of broader efforts to reduce early marriage.